Enhanced Transparency and Resistive Switching Characteristics in AZO/HfO2/Ti RRAM Device via Post Annealing Process - Yuseong Jang; Chanmin Hwang; Sanggyu Bang; Hee-Dong Kim (Inorganics)
As interest in transparent electronics increases, ensuring the reliability of transparent RRAM (T-RRAM) devices, which can be used to construct transparent electronics, has become increasingly important. However, defects and traps within these T-RRAM devices can degrade their reliability. In this study, we investigated the improvement of transparency and reliability of T-RRAM devices with an AZO/HfO2/Ti structure through rapid thermal annealing (RTA) at 450 °C for 60 s in a nitrogen atmosphere. The device without RTA exhibited a low transmittance of 30%, whereas the device with RTA showed a significantly higher transmittance of over 75%. Furthermore, the device operated at lower current levels after RTA, which resulted in a reduction in its operating voltages, and the forming, setting, and reset voltages changed from 3.3, 2.4, and −5.1 V, respectively, to 2, 1, and −2.7 V. This led to an improvement in the endurance characteristics of the device, which thereby suggests that these improvements can be attributed to a reduction in the defects and trap density within the T-RRAM device caused by RTA.